Meritev življenjskega časa nevtronov - Koncilja, Maks (Matrika, 2022)
According to the Standard model, free neutron decay is a fundamental example of ?$β^-$? nuclear decay. The neutron decay time of about 15 minutes has been the subject of many studies since the fifties. It is determined in two main experimental ways: by the beam method and the bottle method. Experimental methods give results that differ by ?$Δ τ_n = 8.6$? s.
Keywords: decay time; fizika osnovnih delcev; neutrons; nevtroni; physics of elementary particles; razpadni čas